Computational chemistry - Eldik, Rudi van; Puchta, Ralph (Advances in inorganic chemistry, 2019)
'Computational Chemistry, ' Volume 73 in the Advances in Inorganic Chemistry series, presents timely and informative summaries on current progress in a variety of subject areas. This acclaimed serial features reviews written by experts in the field, serving as an indispensable reference to advanced researchers that empowers readers to pursue new developments in each field. Users will find this to be a comprehensive overview of recent findings and trends from the last decade that covers various kinds of inorganic topics, from theoretical oriented supramolecular chemistry, to the quest for accurate calculations of spin states in transition metals. Key Features: Features comprehensive reviews on the latest developments in computational studies in inorganic chemistry; Includes contributions from leading experts in the field of inorganic reaction mechanisms; Serves as an indispensable reference to advanced researchers in many related fields. Readership: Chemists interested in classical inorganic chemistry, computational chemists interested in the application of their methods to various kinds of applied inorganic chemistry. --